2019
DOI: 10.21203/rs.2.17545/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The metabolome as a link in the genotype-phenotype map for peroxide resistance in the fruit fly, Drosophila melanogaster

Abstract: Background Genetic association studies that seek to explain the inheritance of complex traits typically fail to explain more than a small fraction of the heritability of the trait under study. Thus we are left with a gap in the map from genotype to phenotype. Several approaches have been used to fill this gap, including those that attempt to map endophenotype such as the transcriptome, proteome or metabolome, that underlie complex traits. Here we used metabolomics to explore the nature of genetic variation for… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 86 publications
0
7
0
Order By: Relevance
“…A set of 20 Drosophila Genetic Reference Panel (DGRP) (Mackay et al, 2012) strains were obtained from the Bloomington Drosophila Stock Center. All flies were maintained at low density on standard yeast–sucrose–glucose–cornmeal medium as described in (Harrison et al, 2020), in incubators at 24°C on a 12h: 12h light–dark cycle at ~50% humidity. All phenotypic assays and targeted metabolomic sampling were performed in two experimental blocks three months apart, with 11 DGRP strains in the first block and nine strains in the second.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A set of 20 Drosophila Genetic Reference Panel (DGRP) (Mackay et al, 2012) strains were obtained from the Bloomington Drosophila Stock Center. All flies were maintained at low density on standard yeast–sucrose–glucose–cornmeal medium as described in (Harrison et al, 2020), in incubators at 24°C on a 12h: 12h light–dark cycle at ~50% humidity. All phenotypic assays and targeted metabolomic sampling were performed in two experimental blocks three months apart, with 11 DGRP strains in the first block and nine strains in the second.…”
Section: Methodsmentioning
confidence: 99%
“…These strains, which together offer a snapshot of current genetic variation within a single population, vary widely in diverse phenotypes (Mackay et al, 2012). Multiple studies have established extensive variation for metabolome profiles in the DGRP (Harrison et al, 2020; Hoffman et al, 2014), and recent work has mapped genetic variation for metabolite levels (Jin et al, 2020; Zhou et al, 2020). The fact that each strain within the DGRP is highly inbred allows us not only to obtain precise genotype‐specific estimates of lifespan and other demographic parameters but also to collect longitudinal measures of metabolome profiles.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in Drosophila have shown that the metabolome is a predictive biomarker of genotypes under stressful situations. 51 In a study of diet restriction in Drosophila, Promislow and colleagues showed that the treatment not only made flies live longer, but also reversed agerelated changes in the metabolome. 52 In a followup study of the effects of dietary restriction across almost 200 inbred strains of flies, Promislow and colleagues used metabolomic profiles to successfully predict whether diet restriction would increase or decrease lifespan.…”
Section: Metabolomics In the Search For Biomarkers And Mechanisms Of Agingmentioning
confidence: 99%
“…Evolution of gene expression is known to exhibit selective constraints [77,78], thereby supporting specific phenotypic outcomes such as changes in morphology [79] and lifespan [80]. Similarly, comparative studies on molecule abundance by metabolite profiling have been utilized to describe the genotype to phenotype relations in model organisms [81,82]. Accordingly, we aimed to explain lifespan differences among these natural populations of closely related yeast isolates by analyzing their endophenotype differences that include gene expression variation (transcriptomics) and differences in their metabolite levels (metabolomics).…”
Section: Endophenotype Variation Across Wild Isolatesmentioning
confidence: 99%
“…In fact, gene expression variation has repeatedly been postulated to play a major role in adaptive evolution and phenotypic plasticity [74,75], as well as specific phenotypic outcomes such as changes in morphology [76] and lifespan [77]. Similarly, comparative studies of metabolite profiles have been utilized to describe the genotype to phenotype relations in model organisms [78,79]. Accordingly, we aimed to explain lifespan differences among these wild-derived yeast isolates by analyzing their gene expression variation (based on transcriptomics analyses) and differences in their metabolite levels (based on metabolomics analyses).…”
Section: Endophenotype Variation Across Wild Isolatesmentioning
confidence: 99%